2021
DOI: 10.1002/jmv.26769
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 nucleocapsid protein intranasal inoculation induces local and systemic T cell responses in mice

Abstract: SARS‐CoV‐2 nucleocapsid (N) protein has been proposed as a good vaccine target. N‐specific T cells were observed in SARS‐CoV‐2 N immunized mice and COVID‐19 convalescents. It is of importance to identify the T cell responses triggered by SARS‐CoV‐2 N protein. Intradermal immunization with SARS‐CoV N protein was demonstrated to elicit non‐protective T cell responses which may be avoided by intranasal vaccination. Therefore, we conducted intranasal vaccination of BALB/c mice with recombinant adenovirus type‐5 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 12 publications
(17 reference statements)
0
25
0
1
Order By: Relevance
“… Type Vaccine Target Route (no. of doses) Animal used Ad-vectored vaccine ChAd-SARS-CoV-2-S S protein IN (1) hACE2 mice 33 , 43 and rhesus macaques 42 ChAd-SARS-CoV-2-S S protein IM or IN, (1) Golden Syrian hamsters 35 AdCOVID RBD protein IN (1) Mice 44 Ad5.SARS-CoV2-S1 S1 protein IN or SC, (1) Mice 45 ChAdOx1 S protein IM or IN, (1 or 2) Ferrets 47 , hamsters and rhesus macaques 46 Ad5-nCoV Full-length S protein IM or IN, (1); or oral + IN, simultaneously, (1) Mice and ferrets 38 Ad5-S-nb2 S protein IM or IN, (1) Mice and rhesus macaques 39 Ad5‐N N protein IN (2) Mice 52 AdC7-S, AdC7-RBD and AdC7-RBD-tr2 S, RBD or tandem-repeat dimeric RBD IM or IN, (2) hACE2 mice 50 S and N proteins SC or IN, (1) Mice 51 Lentivirus-vectored vaccine S protein IP + IN (2); or IM + IN (2) Mice and golden hamsters 57 S protein IM + IN, (2) hACE2 mice 58 Influenza virus-vectored vaccine ∆NA(RBD)-Flu virus RBD pro...…”
Section: Recent Progress In the Development Of Intranasal Covid-19 Vaccinesmentioning
confidence: 99%
“… Type Vaccine Target Route (no. of doses) Animal used Ad-vectored vaccine ChAd-SARS-CoV-2-S S protein IN (1) hACE2 mice 33 , 43 and rhesus macaques 42 ChAd-SARS-CoV-2-S S protein IM or IN, (1) Golden Syrian hamsters 35 AdCOVID RBD protein IN (1) Mice 44 Ad5.SARS-CoV2-S1 S1 protein IN or SC, (1) Mice 45 ChAdOx1 S protein IM or IN, (1 or 2) Ferrets 47 , hamsters and rhesus macaques 46 Ad5-nCoV Full-length S protein IM or IN, (1); or oral + IN, simultaneously, (1) Mice and ferrets 38 Ad5-S-nb2 S protein IM or IN, (1) Mice and rhesus macaques 39 Ad5‐N N protein IN (2) Mice 52 AdC7-S, AdC7-RBD and AdC7-RBD-tr2 S, RBD or tandem-repeat dimeric RBD IM or IN, (2) hACE2 mice 50 S and N proteins SC or IN, (1) Mice 51 Lentivirus-vectored vaccine S protein IP + IN (2); or IM + IN (2) Mice and golden hamsters 57 S protein IM + IN, (2) hACE2 mice 58 Influenza virus-vectored vaccine ∆NA(RBD)-Flu virus RBD pro...…”
Section: Recent Progress In the Development Of Intranasal Covid-19 Vaccinesmentioning
confidence: 99%
“…In the COVID-19 context, the main transgene of choice has been the SARS-CoV-2 structural surface glycoprotein-coding gene (spike protein), either whole or partial [16]. Nonetheless, the nucleocapsid protein (N) has also been the target of some studies, either alone or in combination with the S protein [17][18][19].…”
Section: The "Trojan Horse" Technologymentioning
confidence: 99%
“…Although the majority of vaccines in development are focused on the S protein, the SARS-CoV-2 N protein has also been proposed as a promising vaccine component (Dutta et al, 2020). Studies have shown that the N protein of SARS-CoV-2 can elicit strong humoral and cellular immunity (Ferretti et al, 2020;He et al, 2021;Ni et al, 2020). Notably, a recent study by Dangi et al (2021) found that a spike-based vaccine does not provide acute protection to the central nervous system; however, only when co-administered with a spike-based vaccine and a nucleocapsid-based vaccine, protection against distal viral dissemination to the nervous system was observed.…”
Section: Introductionmentioning
confidence: 99%